2019
DOI: 10.3390/ma12152354
|View full text |Cite
|
Sign up to set email alerts
|

Xenon Diffusion Mechanism and Xenon Bubble Nucleation and Growth Behaviors in Molybdenum via Molecular Dynamics Simulations

Abstract: The behaviors of xenon in molybdenum were studied using molecular statics andmolecular dynamics simulations. The diffusion mechanism of xenon atoms was studied combiningmolecular dynamics, nudged elastic band, and temperature-accelerated dynamics methods. Thevacancy-assisted diffusion mechanism was analyzed and the corresponding energy barriers werecalculated. The clustering process of scattered xenon atoms was studied at an elevated temperature.Xenon bubbles were observed to form when the concentration of xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A similar phenomenon occurred while studying Mo. Zhang et al [16] studied the clustering process of Xe atoms dispersed in Mo at high temperatures. They observed the formation of Xe bubbles when the concentration of Xe atoms exceeded the threshold concentration value.…”
Section: Nucleation Of Xe/kr Cluster In Uo2-containing Point Defectsmentioning
confidence: 54%
See 1 more Smart Citation
“…A similar phenomenon occurred while studying Mo. Zhang et al [16] studied the clustering process of Xe atoms dispersed in Mo at high temperatures. They observed the formation of Xe bubbles when the concentration of Xe atoms exceeded the threshold concentration value.…”
Section: Nucleation Of Xe/kr Cluster In Uo2-containing Point Defectsmentioning
confidence: 54%
“…Consequently, several separation effect experiments have been proposed to simplify complex material systems by describing the physical processes of one or more fission gases to elucidate the underlying behavioural mechanisms. Thus, Zhang et al [16] briefly explained the mechanism of UO 2 by simulating molybdenum.…”
Section: Introductionmentioning
confidence: 99%
“…Shenyang Hu et al [2] pointed out three possible mechanisms as responsible for nanobubble superlattice formation: elastic interaction, one-dimensional migration of selfinterstitial atoms, and dislocation punch out. Several theoretical works can be found in the literature [2,[5][6][7][8] exploring such mechanisms mostly under the assumption that they * pascuet@cnea.gov.ar may be due to overpressurized bubbles. Nevertheless, Salvato et al [9] recently found that, at low burnup, i) nanobubble lattice forms preferentially at grain boundaries and extends to the grain interior with increasing irradiation dose, and ii) bubbles are extremely underpressurized, suggesting its void-like nature.…”
Section: Introductionmentioning
confidence: 99%